Project meeting and guidelines: the impact on time performance of construction projects in Malaysia - Zulkiflee Abdul-Samad; Fakhrul Ridzuan Mokhtar; Hafez Salleh (Penerbit Universiti Kebangsaan Malaysia, 2023)
A project meeting is an event in which stakeholders communicate amongst themselves to meet expectations in the projects by follow up, update, and get feedback. It is a platform for the team to communicate in any projects to serve the purpose of the meeting. As there is a limited study from the literature on the time performance of the project meeting, it is important to determine whether the impact of the project meeting contributes significantly to project time performance or leads to time waste and affects the project time performance. This qualitative study investigates the most significant factors that impact the project meeting to project time performance. Data analysis was obtained from interviews with twenty-seven project managers in the construction industry among local property developers based in Klang Valley, West Malaysia. The study using nvivo technique of analysis revealed most of the project managers agreed scheduling project meetings will improve time performance. The study also proposed guidelines for project meetings incorporating insightful general elements of meetings and time monitoring by incorporating project time spend and analysis of time spent that will assist the project manager to manage meetings efficiently. The findings revealed most of the project managers agreed that the presence of guidelines for meetings helps to guide meetings efficiently and enhance time project performance.